The effect of Jati Belanda (Guazuma ulmifolia Lamk) leaves extract on histopathology of rat’s kidney - Royhan Rozqie; Maulina Diah; Woro Rukmi (Pusat Kedokteran Tropis, 2012)
Introduction: “Jati Belanda”(Guazumaulmifolia Lamk) is a common tropical plant that its leaves extract has long been used traditionaly to treat some tropical diseases and also to reduce body weight as slimming herbs in some of tropical countries. However, the side effect of the administration of“Jati Belanda”leaves extract on themost sensitive excretory organ, the kidney is still notwell documented.Objectives: To study the effect of the oral administration of “Jati Belanda” (Guazuma ulmifolia Lamk.) leaves extract on the histopathology of the kidney.Methods: The study was a pretest and posttest experimental design using four groups of three rat. The study was a pretest and posttest experimental design using four groups of three rat. The exctract of “Jati Belanda” leaves was prepared by boilling of a certain weight of dried “Jati Belanda” leaves in 200 ml of destilated water until the volume of the water became 100 ml. Rat in group I was a control group which were given destilated water, group II were given 0,53 g/100 ml extract, group III were given 1,06 g/100 ml extract and group IV were given 2,12 g/100 ml extract, and the histopathological changes of the rat kidney before, 1 day and 7 days after administration of the extract were compared.Results: Histopathological changes were found in rat kidney following single dose treatment while the control group was not. At one day after administration, mesangial cells proliferation was found in 33,3% of rat in group II and 33,3% of rat in group III, while congestion of blood vessels was found in 66,6% of rat in group III and all rats at the highest dose, group IV. Meanwhile, after 7 days, congestion of micro-vessels was found in all rats of group II, III and IV. Moreover, necrosis of cells was found in 33,3% of rat in group III and infiltration of inflammation cell was found in 66,6% of rat in group IV.Conclusion: A single dose treatment of “Jati Belanda” leaves extract caused histopathological changes on rat kidney. The changes include increased in mesangial cell proliferation, congestion of renal blood vessels in the glomerulus or tubulus, inflamatory cell infiltration and tissue necrosis.Keywords: herbal medicine, “Jati Belanda” Guazuma ulmifolia Lamk. Histopathology, kidney.